Ageratina neblinensis (Asteraceae, Eupatorieae), una nueva especie para el norte del Perú. - Montoya-Quino, J.F. (2018)
As a result of field work on the vegetation of the northern Peruvian Andes, a new species of Ageratina Spach subgen. Andinia R.M. King & H. Rob. is described for the montane rain forests of the Department of Cajamarca (Peru). Description, illustrations and a key to separate the nor-Peruvian Andinia species, studied in different herbaria, are presented.